PSMC1 variant causes a novel neurological syndrome. Issue 4 (3rd August 2022) - Aharoni, Sarit; Proskorovski‐Ohayon, Regina; Krishnan, Ramesh Kumar; Yogev, Yuval; Wormser, Ohad; Hadar, Noam; Bakhrat, Anna; Alshafee, Ismael; Gombosh, Maya; Agam, Nadav; Gradstein, Libe; Shorer, Zamir; et al.
Abstract: Proteasome 26S, the eukaryotic proteasome, serves as the machinery for cellular protein degradation. It is composed of the 20S core particle and one or two 19S regulatory particles, composed of a base and a lid. To date, several human diseases have been associated with mutations within the 26S proteasome subunits; only one of them affects a base subunit. We now delineate an autosomal recessive syndrome of failure to thrive, severe developmental delay and intellectual disability, spastic tetraplegia with central hypotonia, chorea, hearing loss, micropenis and undescended testes, as well as mild elevation of liver enzymes. None of the affected individuals achieved verbal communication or ambulation. Ventriculomegaly was evident on MRI. Homozygosity mapping combined with exome sequencing revealed a disease‐associated p.I328T PSMC1 variant. Protein modeling demonstrated that the PSMC1 variant is located at the highly conserved putative ATP binding and hydrolysis domain, and is suggested to interrupt a hydrophobic core within the protein. Fruit flies in which we silenced the Drosophila ortholog Rpt2 specifically in the eye exhibited an apparent phenotype that was highly rescued by the human wild‐type PSMC1, yet only partly by the mutant PSMC1, proving the functional effect of the p.I328T disease‐causing variant. Abstract : We demonstrate through molecular genetic studies that a novel human neurological syndrome is caused by bi‐allelic variant in PSMC1, encoding a component of the base unit of the eukaryotic proteasome. Our functional studies in fruit flies validate pathogenicity of the variant: phenotypic effects of abrogation of the PSMC1 Drosophila ortholog (Rpt2) were fully reversed through complementation studies with the wild‐type human PSMC1 yet not with the mutant PSMC1.